The Relationship Between School Principal’s Managerial Skills And School Principal’s Leadership With The Performance Of Primary School Teachers In Palangka Raya - Holten Sion; Rina Wahyuni (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
This research aims to analyze and describe the relationship between school principals' managerial skills and principals' leadership with the performance of primary school teachers in the Palangka Raya city. The research method used is a quantitative method with a correlational design. The population includes all primary school teachers in the Palangka Raya city, totaling 2034 people. The research sample was 291 taken using probability random sampling and using the Slovin formula. The data collection technique for school principals' managerial skills was carried out by distributing a questionnaire consisting of 18 questions. The principal's leadership data collection technique was carried out by distributing a questionnaire consisting of 22 questions. Meanwhile, teacher performance data was collected by recording documents and documents of each teacher's performance scores. The data analysis technique used is product moment correlation which consists of: (a) partial (simple) correlation technique and (b) simultaneous (multiple) correlation technique. Research results: (1) the principal's managerial skills have a positive and significant relationship with teacher performance, with a correlation coefficient of 0.541; (2) principal leadership has a positive and significant relationship with teacher performance, with a correlation coefficient of 0.587; and (3) the principal's managerial skills and the principal's leadership together have a positive and significant relationship with the teacher performance, with a correlation coefficient of 0.654.